2022
DOI: 10.1016/j.nephro.2021.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Vascularite leucocytoclasique et néphrite interstitielle aiguë après vaccin à SARS-CoV-2 inactivé

Abstract: Les vaccins contre le SRAS-CoV-2 sont administrés dans le monde entier. La plupart des effets secondaires sont légers et spontanément résolutifs, avec peu de cas signalés de réactions graves. Nous rapportons un cas de vascularite leucocytoclasique avec insuffisance rénale aiguë à la suite d’un vaccin à SARS-CoV-2 inactivé, unique pour sa présentation visuelle spectaculaire et sa réponse rapide au traitement. Il s’agit d’un homme âgé de 58 ans présentant de la fièvre, des arthralgies et un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Case 11[ 35 ] had a history of taking non-steroid anti-inflammation drugs (NSAIDs) for muscle pain. In addition to leukocyturia and proteinuria, case 8 [ 32 ] had a symptom of vascular purpura, with multiple necrotic lesions involving the hands, arms, thighs, and feet and a skin biopsy suggesting leukocytoclastic vasculitis. Follow-up data were obtained for all patients, and 9 of them responded well to treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Case 11[ 35 ] had a history of taking non-steroid anti-inflammation drugs (NSAIDs) for muscle pain. In addition to leukocyturia and proteinuria, case 8 [ 32 ] had a symptom of vascular purpura, with multiple necrotic lesions involving the hands, arms, thighs, and feet and a skin biopsy suggesting leukocytoclastic vasculitis. Follow-up data were obtained for all patients, and 9 of them responded well to treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Components in the SARS-CoV-2 vaccines, such as polyethylene glycol, are also known to be immunogenic and can trigger hypersensitivity-like reactions [ 54 ]. Eight patients [ 25 , 27 , 31 , 32 , 35 , 37 , 38 , 45 ] developed leukocyturia after vaccination, and two patients [ 27 , 28 ] had peripheral eosinophilia. Therefore, we suspected AIN was an allergic reaction triggered by the vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports have highlighted intriguing connections between LCV and various comorbidities or triggers. For instance, there have been cases where LCV flares were precipitated by factors such as influenza vaccination, certain infections such as Mycoplasma, and medications such as vancomycin or warfarin [11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…LCV case with a history of ischemic heart disease exacerbated by an influenza vaccine, leading to acute renal failure requiring hemodialysis Ippoliti et al [14] LCV occurrence post-heart transplant alongside immunotherapy, indicating a potential link between immunosuppression and vasculitis Rao et al [15] LCV manifestation following Mycoplasma-induced upper respiratory tract superinfection, characterized by conspicuous skin lesions Pingili et al [16] Diffuse LCV and acute renal failure observed after intravenous vancomycin administration, highlighting a medicationtriggered LCV case Elantably et al [17] LCV diagnosis subsequent to warfarin prescription for rheumatic heart disease, exhibiting classic manifestations of LCV Missoum et al [18] Vaccine-induced LCV linked to the inactivated COVID-19 vaccine, diagnosed due to lack of alternative etiology postvaccination Orlando et al [19] LCV coexisting with heart failure showing reduced ejection fraction due to ANCA-negative vasculitides, emphasizing the cardiac implications of vasculitis Golan et al [20] Systemic vasculitis in a patient with Sjögren's syndrome, leading to exertional dyspnea and orthopnea, showing reversibility post-immunosuppressant therapy and improved ejection fraction ANCA: antineutrophil cytoplasmic antibody; LCV: leukocytoclastic vasculitis Among medications, amiodarone has been implicated in vasculitis, specifically LCV, although the exact mechanisms remain less understood [3][4][5]. Current literature suggests the potential involvement of immune complexes formed by amiodarone or its metabolites, triggering an inflammatory response within blood vessel walls, thereby leading to vasculitis [3,4].…”
Section: Study Key Findingsmentioning
confidence: 99%